Beyond Angiogenesis: The Multitasking Approach of the First PEGylated Vascular Endothelial Growth Factor (CdtVEGF) from Brazilian Rattlesnake Venom - Ferreira, Isabela; Oliveira, Isadora; Bordon, Karla; Reis, Mouzarllem; Wiezel, Gisele; Sanchez, Caroline; Santos, Luísa; Santos-Filho, Norival [UNESP]; Pucca, Manuela [UNESP]; Antunes, Lusânia; Lopes, Daiana; Arantes, Eliane (MDPI, 2023)
A pioneering study regarding the isolation, biochemical evaluation, functional assays and first PEGylation report of a novel vascular endothelial growth factor from Crotalus durissus terrificus venom (CdtVEGF and PEG-CdtVEGF). CdtVEGF was isolated from crude venom using two different chromatographic steps, representing 2% of soluble venom proteins. Its primary sequence was determined using mass spectrometry analysis, and the molecule demonstrated no affinity to heparin. The Brazilian crotalid antivenom recognized CdtVEGF. Both native and PEGylated CdtVEGF were able to induce new vessel formation and migration, and to increase the metabolic activity of human umbilical endothelial vascular cells (HUVEC), resulting in better wound closure (~50% within 12 h) using the native form. CdtVEGF induced leukocyte recruitment to the peritoneal cavity in mice, with a predominance of neutrophil influx followed by lymphocytes, demonstrating the ability to activate the immune system. The molecule also induced a dose-dependent increase in vascular permeability, and PEG-CdtVEGF showed less in vivo inflammatory activity than CdtVEGF. By unraveling the intricate properties of minor components of snake venom like svVEGF, this study illuminates the indispensable significance of exploring these molecular tools to unveil physiological and pathological processes, elucidates the mechanisms of snakebite envenomings, and could possibly be used to design a therapeutic drug.
Keywords: Crotalus durissus terrificus; neutrophilic recruitment; PEGylation; vascular permeability; VEGF